(untitled) (Revista Brasileira Multidisciplinar, 2024)
Depression is characterized by the loss or decrease of interest and pleasure in life, the feeling of sadness and low self-esteem, generating anguish and prostration, excessive tiredness, body aches, anxiety and insomnia. Amitriptyline hydrochloride is a tricyclic antidepressant, a highly effective drug in the treatment of depression, proven by considerable clinical studies, and a medicine of great importance in the pharmaceutical market. In this context, pharmaceutical equivalence aims to promote comparative quality tests between the reference medicine and the test medicine. Therefore, the objective of this study was to compare the quality of amitriptyline tablets available on the market, classified as generic and reference medicines, through pharmacopoeial analyses. Quantitative analyzes were carried out using ultraviolet spectrophotometry. The proven samples presented adequate quality in terms of weight determination, disintegration, uniformity of unit doses, dosage and dissolution tests, complying with pharmacopoeial parameters and presenting guaranteed efficacy and safety of use. However, when comparing the dissolution profiles, the 75 mg reference sample presented values ​​close to 80% dissolution in times less than 15 minutes, while the 75 mg generic and 25 mg reference samples required close to 60 minutes. to achieve this value. To compare the profiles, the similarity factor (f2) between samples AxB and AxC was calculated, which were 10.58 and 30.65, respectively. Therefore, the samples did not demonstrate pharmaceutical equivalence under the conditions tested.